Organic–inorganic hybrid salt and mixed ligand Cr(III) complexes containing the natural flavonoid chrysin: Synthesis, characterization, computational, and biological studies - Alem, Mamaru Bitew; Desalegn, Tegene; Damena, Tadewos; Bayle, Enyew Alemayehu; Koobotse, Moses O.; Ngwira, Kennedy J.; Ombito, Japheth O.; Zachariah, Matshediso; Demissie, Taye B. (Frontiers in Chemistry, 2023)
Organic-inorganic hybrid salt and mixed ligand Cr(III) complexes (Cr1 and Cr2) containing the natural flavonoid chrysin were synthesised. The metal complexes were characterised using UV-Vis, FTIR, MS, SEM-EDX, XRD and molar conductance measurements. Based on experimental and DFT/TD-DFT calculations, octahedral geometries for the synthesized complexes were suggested. The powder XRD analysis confirms that the synthesised complexes were polycrystalline with orthorhombic and monoclinic crystal systems having average crystallite sizes of 21.453 and 19.600 nm, percent crystallinity of 51 and 31.37% and dislocation density of 2.324 × 10−3 and 2.603 × 10-3 nm-2 dislocation density for Cr1 and Cr2, respectively. The complexes were subjected to cytotoxicity, antibacterial and antioxidant activity studies. The in-vitro biological studies were supported with quantum chemical and molecular docking computational studies. Accordingly, Cr1 showed significant cytotoxicity to the MCF-7 cell line with IC50 8.08 μM compared to Cr2 (IC50 = 30.85 μM) and cisplatin (IC50 = 18.62 μM), while Cr2 was found to exhibit better antibacterial activity than Cr1. The higher EHOMO (-5.959 eV) and dipole moment (10.838 Debye) values of Cr2 obtained from the quantum chemical calculations support the in-vitro antibacterial activities recorded. The overall results indicated that Cr1 is a very promising cytotoxic drug candidate.